Neoadjuvant therapy or upfront surgery? A systematic review and meta-analysis of T2N0 esophageal cancer treatment options. (June 2018) - Mota, F.C.; Cecconello, I.; Takeda, F.R.; Tustumi, F.; Sallum, R.A.A.; Bernardo, W.M.
Abstract: Background: Esophageal carcinoma usually shows poor long-term survival rates, even when esophagectomy, the standard curative treatment is performed. As a result, there has been increasing interest in the neoadjuvant therapy, which could potentially downstage cancer, eliminate micrometastasis and ergo increase resectability and curative (R0) resection. Currently, for the earliest stage esophageal cancers, most guidelines point out to the role of endoscopic treatment, and for T1bN0 upfront surgery. For locally advanced cases, several studies have demonstrated the benefits of neoadjuvant therapy to increase resectability. For clinical stage T2N0 esophageal cancer, there is no consensus as to the optimal treatment strategy. Methods: A systematic review and meta-analysis was performed to compare neoadjuvant therapy with surgery alone on clinical stage T2N0 esophageal cancer patients, concerning overall survival, recurrence, post-operative mortality, anastomotic leak, and R0 resection rate. Results: For overall survival at the mean follow-up point, the neoadjuvant therapy was not associated to a higher probability of survival than upfront surgery in cT2N0 patients (risk difference: 0.00; 95% CI: −0.09, 0.09). There was no difference between neoadjuvant therapy and primary surgery concerning recurrence (risk difference: 0.21; 95% CI: −0.03, 0.45); perioperative mortality (risk difference: 0.00; 95% CI: −0.02, 0.01); and risk for anastomotic leak (risk difference: −0.08; 95% CI: −0.21, 0.05). Pooled data showed that neoadjuvant therapy was associated to a higher risk for positive margins after resection (risk difference: 0.04; 95% CI: 0.02, 0.06). Conclusions: This review showed that neoadjuvant therapy is not associated to better results than surgery alone, for the management of clinical stage T2N0 esophageal cancer patients, concerning overall survival, recurrence rate, perioperative mortality, anastomotic leak, and seems to be associated to a higher risk for resection with positive margins. Highlights: Neoadjuvant therapy. Surgery upfront. Systematic review. Meta-analysis. Survival.